The perspective of using 3D-modeling in the designing of technological solutions for chassis design - L.S, Abdullah; V.A, Kukushkina; E.A, Kantaryuk (International Journal of Engineering and Technology, 2018)
In the modern world 3D-technologies plays an important and significant role in almost every spheres of human life. This is particularly pronounced in industry. Perspectives of using these technologies allow optimizing the production of products of varying complexity, reducing production time and reducing the possibility of defects in the early stages of designing. For the showing the application of 3D modeling its application in vehicle designs considered in this paper. For this purpose a vehicle chassis is designed and then the tension distribution of chassis in the bump condition and its analysis are provided.